Matemática e Cartografia: como a cartografia pode contribuir no processo de ensino-aprendizagem da matemática? - ROCHA, Maria Lúcia Pessoa Chaves (Universidade Federal do Pará, 2012)
Mathematics Teaching is being under changes trough the previous years in order to make learning more profitabe and less disgusting to students, contributing thus, to the improvement of their learning. Search for.the improvement of mathematics through alternative methodologies is being the major approach of the moment. Mathematics modeling represents one of those methodolieges. Through the use their creeds and instructions, the present paper aims to associate cartographys a math model, the contenporâneous tools which are the basis of teaching learning process of math. Cartography termed as a set of comprehensive technologies and graphic representation of the earth surface which basis are assentially mathematic, have constitued a great tool of date representation and information of the surface by several professionals, this paper is for its application through mathematics modeling to the process of enforcenent of teaching-learning process of math.